Проблеми здорового харчування та їхнє висвітлення в інформаційних мобільних застосунках - Коваленко, А. В. (ХНУРЕ, 2024)
The present investigation is dedicated to the examination of mobile applications aimed at addressing issues pertaining to healthy dietary practices. An exploration into the significance of sound nutritional habits within the human sphere is conducted. Central to the inquiry is the identification of nutritional disparities as the principal concern addressed by informational applications. The primary avenues of digital interventions in the realm of healthy nourishment are delineated. Furthermore, the merits of employing a chatbot as a potent instrument for tailoring interactions to individual users while concurrently accessing a broad demographic are substantiated.
Keywords: проблеми здорового харчування; харчування